Pendidikan Akhlak Remaja bagi Keluarga Kelas Menengah Perkotaan - Munthoha, Payiz Zawahir; Wekke, Ismail Suardi (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
Islamic education is not only related to contents, methods, and practices. Meanwhile, the environment of educators and learners is also worth to investigate. Every family has a view according to their circumstances. Hence, an identification of the educational environment is needed to provide adaptation for the interests of Islamic education. This research was conducted using a qualitative approach in Bandung, West Java. Interviews and non-participant observations were conducted during data collection. The results showed that there was a need for Muslims in connection with Islamic education, especially in urban areas. Parents worried if their children were not equipped with religious knowledge during the process of adaptation and socialization. Furthermore, the Muslim family also requiredchildren to learn reading and writing the Quran from an early age. This was intended to equip them with the skills of reading the holy Qurâan. Finally, it also described the eight social skills that Muslim families trained for their sons and daughters.Â Ø¥Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ§ ØªØªØ¹ÙÙ ÙÙØ· Ø¨Ø§ÙÙØ§Ø¯Ø© ÙØ§ÙØ·Ø±ÙÙØ© ÙØ§ÙØªØ·Ø¨ÙÙ. ÙØ§ÙØ¹ÙØ³ Ø¥Ù Ø¨ÙØ¦Ø© Ø§ÙÙØ¹ÙÙÙÙ ÙØ§ÙÙØªØ¹ÙÙÙÙÙ Ø£ØµØ¨ØØª Ø¸Ø±ÙÙØ§ Ø®Ø§ØµØ©. ÙÙÙ Ø¬Ø§ÙØ¨ Ø¢Ø®Ø±Ø ÙÙÙ Ø£Ø³Ø±Ø© Ø±Ø¤ÙØªÙØ§ Ø¨ÙØ§ ÙÙØ§ ÙÙ Ø§ÙØ¸Ø±ÙÙ ÙØ§ÙØ£ØÙØ§Ù Ø§ÙÙØÙØ·Ø© Ø¨ÙØ§. ÙØ°Ø§ ÙÙØØªØ§Ø¬ Ø¥ÙÙ ØªØØ¯ÙØ¯ ÙØªØ¹ÙÙÙ Ø§ÙØ¨ÙØ¦Ø© Ø§ÙØªØ±Ø¨ÙÙØ© ÙØ£Ø¬Ù Ø§ÙØªÙÙÙÙ ÙÙÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ©. Ø¹ÙÙØ¯ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¨Ø§ÙÙØ¯Ø®Ù Ø§ÙÙÙÙÙ ÙÙ ÙØ¯ÙÙØ© Ø¨Ø§ÙØ¯ÙÙØ¬ Ø¬Ø§ÙØ© Ø§ÙØºØ±Ø¨ÙØ©. ÙÙØ¬ÙØ¹ Ø§ÙØ¨ÙØ§ÙØ§Øª ÙÙØ³ØªØ®Ø¯Ù Ø£Ø³ÙÙØ¨ Ø§ÙÙÙØ§Ø¨ÙØ© Ø§ÙØ´Ø®ØµÙØ© ÙØ§ÙÙÙØ§ØØ¸Ø© Ø¨Ø¯ÙÙ Ø§ÙÙØ´Ø§Ø±ÙØ©. Ø¯ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø£Ù ÙÙØ§Ù ØØ§Ø¬Ø© ÙÙÙØ³ÙÙÙÙ Ø¥ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ®Ø§ØµØ© ÙÙ Ø§ÙÙØ¯Ù. ÙØ«ÙØ© Ø§ÙÙØ®Ø§ÙÙ ÙÙ ÙØ¨Ù Ø§ÙØ¢Ø¨Ø§Ø¡ ÙØ§ÙØ£ÙÙØ§Øª ØÙÙ ÙØ§ ÙÙØ²ÙÙØ¯ Ø§ÙØ£Ø¨ÙØ§Ø¡ Ø¨Ø§ÙØªØ¹Ø§ÙÙÙ Ø§ÙØ¯ÙÙÙØ© Ø®ÙØ§Ù ØªÙÙÙÙÙÙ ÙØªØ¹Ø§ÙÙÙÙ Ø¨ØºÙØ±ÙÙ. ÙÙØ§ÙØ´Øª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© ÙØ°ÙÙ Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØªÙ ØªÙØ³ÙÙØª Ø¨ÙØ§ Ø§ÙØ£Ø³Ø±Ø©. ÙÙÙØ³ ÙØ°Ø§ ÙÙØ·Ø ÙØ¥Ù Ø§ÙØ£Ø³Ø±Ø© Ø§ÙÙØ³ÙÙØ© Ø£ÙØ¬Ø¨Øª ÙÙ Ø£Ø¨ÙØ§Ø¦ÙØ§ ØªØ¹ÙÙÙ ÙØ±Ø§Ø¡Ø© Ø§ÙÙØ±Ø¢Ù ÙÙØªØ§Ø¨ØªÙ ÙÙ Ø³ÙÙ ÙØ¨ÙÙØ±. ÙØ§ÙÙØ¯Ù ÙÙÙ ØªØ²ÙÙØ¯ Ø§ÙØ£Ø¨ÙØ§Ø¡ Ø¨ÙÙØ§Ø±Ø© ÙØ±Ø§Ø¡Ø© Ø§ÙÙØ±Ø¢Ù. ÙØ¹Ø±Ø¶Øª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© ÙØ°ÙÙ Ø«ÙØ§ÙÙ ÙÙØ§Ø±Ø§Øª Ø§Ø¬ØªÙØ§Ø¹ÙØ© Ø¯Ø±Ø¨ØªÙØ§ Ø§ÙØ£Ø³Ø± Ø§ÙÙØ³ÙÙØ© Ø¹ÙÙ Ø¬ÙÙØ¹ Ø£Ø¨ÙØ§Ø¦ÙØ§ ÙØ¨ÙØ§ØªÙØ§.